OPTIMALISASI SARANA PRASARANA PENDIDIKAN DALAM PENERAPAN KURIKULUM MERDEKA DI MA MAMBAUL ULUM DAN MA NASY’ATUL MUTA’ALLIMIN GAPURA SUMENEP - Fadilah, Dina Rodiyatil; Marno (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2025)
support the implementation of the Merdeka Curriculum. The aim is to identify effective strategies for planning, utilization, maintenance, monitoring, and evaluation of facilities and infrastructure so that the curriculum implementation can run optimally. The method used is a qualitative approach with semi-structured interviews conducted with the principals of MA Mambaul Ulum and MA Nasy’atul Muta'allimin. The data obtained were thoroughly analyzed to illustrate best practices in infrastructure management. The results show that systematic planning, including the provision of basic facilities, technology integration, teacher training, and student involvement in maintenance, can improve the efficiency of infrastructure use. Additionally, the success of infrastructure management is measured using evaluations based on indicators such as student satisfaction and learning outcome achievements. This research recommends further studies with a broader scope and empirical approaches to ensure the effectiveness of the proposed concepts and the implementation of adaptive solutions in diverse educational contexts.